2022
DOI: 10.3390/ijerph19095567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aroma Foot Massage on Sleep Quality and Constipation Relief among the Older Adults Living in Residential Nursing Facilities

Abstract: This study focused on the effects of aroma foot massage on sleep quality and constipation relief among older adult residents in nursing facilities. This research used a non-equivalent control group and a quasi-experimental design. The participants included 40 older adults aged ≥70 years residing in two nursing facilities in Seoul City. The aroma foot massage nursing intervention consisted of a preparation stage using jojoba carrier (aroma recipe) oil and lavender oil, an aroma foot massage stage, and a finishi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Eight articles (100.0%) [A1-A8] used defecation frequency to measure constipation, followed by four articles (50.0%) [A1,A2,A4,A8] that examined defecation-related characteristics and three articles (37.5%) [A1, A2, A8] that examined the actual condition of constipation. Except for the studies by Park et al [32] [A2] and Kang et al [36] [A7], the frequency of defecation per week was used [A1,A3-A6,A8], and the frequency of defecation was confirmed by the facility's medical records or defecation diary. Furthermore, the included studies identified defecation-related characteristics [A1,A2,A4,A8] such as defecation habits, time required to defecate, associated symptoms, difficulty in defecating, abdominal discomfort and pain, constipation symptoms, and constipation condition [A1,A2,A8] such as constipation, constipation before admission, use of non-pharmacological therapies, use of constipation medications, and use of laxatives.…”
Section: ) Constipation Measurement Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight articles (100.0%) [A1-A8] used defecation frequency to measure constipation, followed by four articles (50.0%) [A1,A2,A4,A8] that examined defecation-related characteristics and three articles (37.5%) [A1, A2, A8] that examined the actual condition of constipation. Except for the studies by Park et al [32] [A2] and Kang et al [36] [A7], the frequency of defecation per week was used [A1,A3-A6,A8], and the frequency of defecation was confirmed by the facility's medical records or defecation diary. Furthermore, the included studies identified defecation-related characteristics [A1,A2,A4,A8] such as defecation habits, time required to defecate, associated symptoms, difficulty in defecating, abdominal discomfort and pain, constipation symptoms, and constipation condition [A1,A2,A8] such as constipation, constipation before admission, use of non-pharmacological therapies, use of constipation medications, and use of laxatives.…”
Section: ) Constipation Measurement Methodsmentioning
confidence: 99%
“…For the content analysis, we divided the articles included in this study into article number, author name and year of publication, study objectives, study subjects, measures used to assess constipation, main results, constipation-related factors (general characteristics, health-related factors, diet-related factors), and intervention characteristics (type, method, target, session, intervention time per session, intervention frequency, intervention duration, intervention provider), and results are shown in Table 2~4 (Appendix 1) [11,[31][32][33][34][35][36][37].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 Indeed, there is an increasing number of clinical trials on massage for different conditions, particular in the diseases of the musculoskeletal system or connective tissue, nervous system, digestive system, gynecological and pediatric diseases, even for some subhealth status with symptoms, signs or clinical findings but not be definitely diagnosed. 7,[11][12][13] More researchers and clinical practitioners are investigating the underlying mechanism(s) of the above clinical efficacy, such as why the intervention can reduce different types of pain. 14,15 The results reported that the functions of massage could be summarized as boosting blood circulation, removing blockages, realigning the musculoskeletal structure, and enhancing the body's natural healing abilities.…”
Section: Introductionmentioning
confidence: 99%